Aftermath of COVID-19: Exploring the Perception of Violence Against Women in the Middle East and North Africa - Pourmehdi, Mansour (Journal of interpersonal violence, 2024)
This article explores the perception of violence against women (VAW) in the Middle East and North Africa in the aftermath of the COVID-19 pandemic using Arab Barometer VI parts 1 and 3 (N = 12,548). Results showed that men and social conservatism were less likely to perceive that the VAW in the community had increased. For religious people, the odds of perceiving violence in the community were higher. Individuals whose jobs were interrupted because of the COVID-19 outbreak were more likely to perceive VAW in the community has increased compared to individuals whose jobs were not interrupted. The strongest predictor of the perception of increased VAW in the community because of COVID-19 was the current economic situation of the country. Those who perceived the economic situation of the country as bad were 1.6 times more likely to believe that VAW has increased. Government handling of the crisis and overall government performance increased the odds of perceiving that VAW has increased. Investigating correlates of VAW as the consequence of the COVID-19 pandemic is crucial because it helps governments, emergency services, and community leaders develop strategies of prevention for future disasters and improve community and institutional reactions.